Desenvolvimento regional da área de livre comércio de Boa Vista e suas implicações socioespaciais a partir de um estudo geoestratégico - Anjos, Jeniffer Natalie Silva dos (2014)
Aiming to introduce a study about the Trade free Area in Boa Vista -RR from the regional integration policy for the Western Amazon perspective, this research discusses the aspects of interdependence in the composition of intra - regional and inter - regional levels resulting from actions regionalization programmed by the national government for the areas that present striking regional differences in its economy compared to other Brazilian regions. Based on the laws of creation and regulation of the free trade area of Boa Vista, this research is based on the design of policies for the development of areas located in lower economic circuits and dependent of scales with specialized economies. Basing on the concept of regional development policies the city of Boa Vista is evaluated as receptor of State actions imposed in a hierarchical level. Under these conditions the special customs regime of free trade area type is reported as an integration policy and failed regional development, presented no more than a compensatory action due the economic inertia and inroad of the state of Roraima. Established on alternative of development sprayed by state and regional elites, little socioeconomic transformations in the city do not result in the efficiency of development model proposed for the Amazon and in particular for Boa Vista.